Risk Factors Associated With Human Papillomavirus Infection, Cervical Cancer, and Precancerous Lesions in Large-Scale Population Screening - Yang, Di; Zhang, Jing; Cui, Xiaoli; Ma, Jian; Wang, Chunyan; Piao, Haozhe (Frontiers in Microbiology, 2022)
Cervical cancer is the most common gynecological malignancy and screening for risk factors with early detection has been shown to reduce the mortality. In this study, we aimed to analyze the characteristics and risk factors of human papillomavirus (HPV) infection and precancerous lesions in women and provide clinical evidence for developing strategies to prevent cervical precancerous lesions and cancer in women. Furthermore, we evaluated the influencing factors for high-risk HPV infection. From April 2018 to December 2021, 10,628 women were recruited for cervical cancer screening at Liaoning Cancer Hospital, Shenyang Sujiatun District Women's and Infants Hospital, Benxi Manchu Autonomous County People's Hospital, and Shandong Affiliated Hospital of Qingdao University. The study participants were tested to determine if they were HPV-positive (HPV+) or underwent thinprep cytology test (TCT) for atypical squamous cells of undetermined significance (ASCUS) and above. Furthermore, colposcopies and biopsies were performed for the histopathological examination. Finally, 9991 cases were included in the statistical analysis, and the factors influencing HPV infection and those related to cervical cancer and precancerous lesions were analyzed. HPV+ infection, high-grade squamous intraepithelial lesion-positive (CINII+) in cervical high-grade intraepithelial neoplasia, and early cervical cancer diagnosis rates were 12.45%, 1.09%, and 95.41%, respectively. The potential risk factors for HPV were education ≤high school, age at initial sexual activity ≤19 years, sexual partners >1, ASCUS and above, non-condom contraception, and HSIL and above. Compared with women aged 56–65 and 35–45 yearsthe HPV infection rate was significantly lower in those aged 46–55 years. Furthermore, ≤high school age, not breastfeeding, ASCUS and above were potential risk factors for cervical cancer and precancerous lesions. In women with HPV infection, ≤high school education level, initial sexual activity at ≤19 years of age, number of sexual partners >1, ASCUS and above, non-condom contraception, HSIL and above were risk factors for HPV infection. Compared with women aged 56–65 years, those aged 35–45 and 46–55 years had significantly lower HPV infection rates, and high school age and below, non-breastfeeding, and ASCUS and above were all potential risk factors for cervical cancer and precancerous lesions.